PENGARUH MODEL PEMBELAJARAN AKTIF TIPE CARD SORT DAN MOTIVASI BELAJAR DALAM MATA KULIAH KETERAMPILAN BERBAHASA INDONESIA KE-SD-AN MAHASISWA PRODI PGSD - Hidayati Azkiya; Muhammad Tamrin (Puitika)
Research begins from the low ability of learning Indonesian Language Skills to elementary school students Elementary School Education Studies. This is seen in the midterm exam results as well as interviews with lecturers of Indonesian Language Skills Speaking to SD-an. The objective of this research is to know the influence of active learning model of card sort type to learning Indonesian Language Skills to Elementary School Primary School Teacher Education Program students. The type of this research is Quasi Eksperimen. Data collection techniques using questionnaires and learning result tests and data analysis techniques with t-test and ANAVA. The results showed that the students' learning outcomes by using the active learning model of card sort type is higher than the conventional learning model both from the whole and from the learning motivation. And there is no interaction of learning model with learning motivation to Indonesian Speaking Skill to SD-an. So it can be concluded that the active learning model of the type of card sort and motivation to learn influence on Indonesian Skills to SD-an.